The Personalization, Communication and Development of Chinese Folk Music under the Background of Globalization - Zhao, Huan (Transactions on Social Science, Education and Humanities Research, 2023)
This study aims to explore the personalization, communication, and development of Chinese folk music under the background of globalization. Under the background of globalization, cultural exchanges and diversified development have brought new opportunities and challenges to Chinese folk music. By analyzing the status and importance of Chinese folk music in the process of globalization, as well as the display of personalized expression forms, this study explores the impact of globalization on Chinese folk music and puts forward the elements for benign development. By exploring new ways of expression and incorporating multicultural elements, Chinese folk music can expand its range of expression and influence. The process of globalization has provided a broad stage for Chinese folk music. At the same time, it is necessary to overcome challenges and maintain the uniqueness and development direction of traditional culture.